2014
DOI: 10.1002/ppul.23117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preterm birth on exercise capacity: A systematic review and meta‐analysis

Abstract: Despite marked deficits in spirometry, preterm-born children have a marginally decreased V˙O2max⁡, which is unlikely to be of great clinical significance. Pediatr Pulmonol. 2015; 50:293-301. © 2014 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 44 publications
4
40
0
Order By: Relevance
“…We used methodologies and data from our three previous systematic reviews . As data for BHR are often not reported in titles or abstracts, we combined several approaches.…”
Section: Methodsmentioning
confidence: 99%
“…We used methodologies and data from our three previous systematic reviews . As data for BHR are often not reported in titles or abstracts, we combined several approaches.…”
Section: Methodsmentioning
confidence: 99%
“…Children born preterm (<37 weeks’ gestation) are at increased risk for respiratory-related morbidity [ 1 , 2 ]. We have also shown reduced lung function of preterm-born school-age children using data from a large cohort study [ 3 ] as well as modest reductions in exercise capacity [ 4 ]. What is unclear is if such respiratory morbidities and decrements in lung function reduce children’s ability to participate in adequate levels of physical activity, possibly secondary to airway obstruction and impaired gas exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm-born individuals make up 10.6% of birth worldwide (40), and they are prone to adverse cardiorespiratory outcomes (4,5) and increased cardio-metabolic risk factors (6). Even though the benefits of physical activity are propagated in health policies (7,8), this systematic review reveals a paucity of studies with preterm populations.…”
Section: Discussionmentioning
confidence: 98%
“…Preterm birth can be regarded as a chronic health condition that has the potential to lead to functional limitations like intellectual disability, cerebral palsy, other motor problems and psychiatric conditions . Additionally, research has shown an increased risk of impaired lung function , reduced cardiorespiratory fitness and more cardio‐metabolic risk factors .…”
Section: Introductionmentioning
confidence: 99%